(untitled) (Bangladesh Journal of Medical Science, 2013)
Pulmonary Lymphangitis carcinomatosis is an unusual metastatic manifestation of Oesophagogastric carcinoma and it occurs due to diffuse spread of the tumour to the pulmonary lymphatic system. We described a case of a 28 year old woman, presenting with gradually progressive dyspnoea and cough where results of Chest X-ray and HRCT thorax were consistent with features of Lymphangitis carcinomatosis. Upper GI endoscopic evaluation showed a tumour originating from oesophagogastric junction and extending to cardia of stomach. Biopsy from tumour revealed adenocarcinoma. As there is no definitive therapy to this condition, patient was managed conservatively only to succumb few days after hospitalisation. DOI: http://dx.doi.org/10.3329/bjms.v12i1.11642 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.96-99